2020
DOI: 10.1002/ldr.3693
|View full text |Cite
|
Sign up to set email alerts
|

Introduced goats reduce diversity and biomass of herbs in Caatinga dry forest

Abstract: Herbivores are considered important drivers of vegetation shifts in rangelands worldwide. In the Brazilian Caatinga years in 16 paired exclosure versus free-access plots.Exclosure of goats caused a small but significant increase in the species diversity and above-ground biomass of herbs that varied strongly with time. Taxonomic dissimilarity between exclosure and free-access was small and due to the turnover of a few species, however, tended to increase with time. Environmental co-variables, such as rainfall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
(63 reference statements)
0
6
0
1
Order By: Relevance
“…In native Caatinga, the effect of grazing by any species should not have significant effects on the vegetation, as long as the relationship between supply and demand for pasture is respected. Under overgrazing conditions, goats and sheep can induce changes in the floristic composition of the Caatinga (23,24) . Santos et al (25) , in studies carried out with species on native pasture and on diet, reported that it is important to determine the strategies for using the materials to increase the results of forage production and animal performance, thus improving the development of ruminant production in the semiarid region.…”
Section: Resultsmentioning
confidence: 99%
“…In native Caatinga, the effect of grazing by any species should not have significant effects on the vegetation, as long as the relationship between supply and demand for pasture is respected. Under overgrazing conditions, goats and sheep can induce changes in the floristic composition of the Caatinga (23,24) . Santos et al (25) , in studies carried out with species on native pasture and on diet, reported that it is important to determine the strategies for using the materials to increase the results of forage production and animal performance, thus improving the development of ruminant production in the semiarid region.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in physical conditions (i.e., increased habitat desiccation) and selection of resprouting species have been proposed as key drivers for community‐level responses to chronic human disturbance in the Caatinga dry forest (Arnan et al, 2018; Barros et al, 2021; Ribeiro et al, 2015; Rito, Arroyo‐Rodríguez, et al, 2017; Rito, Tabarelli, et al, 2017). In our focal landscape, introduced goats have been reported to reduce the biomass and diversity of herb assemblages (Menezes et al, 2020), with a combination of shifting cultivation and goat pressure as the anecdotal drivers for the establishment of assemblages dominated by unpalatable perennial herbs such as Herissantia crispa (Malvaceae). Moreover, leaf‐cutting ants respond positively to human disturbances in this landscape, reducing seedling abundances across extensive foraging areas (Knoechelmann et al, 2020; Siqueira et al, 2017, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The forest is small statured (i.e., mean height of 3.70 m; Barros et al, 2021) with a predominance of Euphorbiaceae and Fabaceae families . Forest stands are permanently exposed to the collection of forest products (e.g., firewood, fodder, and medicinal plants) plus browsing by free-ranging, exotic goats that feed on the native vegetation (Arnan et al, 2018;Menezes et al, 2020). Sandy soils and flat terrain are prevalent in the focal forest stands, with no evidence of recent agricultural activities within the stands (Rito, Arroyo-Rodríguez, et al, 2017).…”
Section: Study Areamentioning
confidence: 99%
“…Trabalhos realizados em diferentes partes do mundo indicam que os caprinos e ovinos possuem um alto custo ecológico para a comunidade de plantas nativas. Recentemente, um estudo realizado no Parque Nacional do Catimbau observou que a exclusão pelos caprinos influenciou na diferenciação taxonômica de algumas espécies das comunidades herbáceas da área com efeito cumulativo ao longo do tempo (Menezes et al 2020). Segundo os trabalhos de Tsuiki et al (2005), realizado numa floresta de Pradarias na China, áreas que apresentavam pastejo leve e moderado exibiam riqueza de espécies de planta semelhantes, diferente do encontrado em áreas com pastejo pesado que mostraram menor riqueza e diversidade de espécies.…”
Section: Discussionunclassified